Examining the association between exposure to various screen time sedentary behaviours and cannabis use among youth in the COMPASS study - Amanda Doggett; Wei Qian; Katelyn Godin; Margaret De Groh; Scott T. Leatherdale (Elsevier, 2019)
Background: Canadian youth are among the top users of cannabis globally. The Canadian federal government identified protecting youth from cannabis-related harms as a key public health objective aligned with the legalization and strict regulation of cannabis. While there are well-established associations between screen time sedentary behaviour (STSB) and alcohol and tobacco use, the association with cannabis use is understudied. The purpose of this study is to examine the association between various types of STSBs and cannabis use in a large sample of Canadian youth. Methods: Using cross-sectional data from 46,957 grade 9 to 12 students participating in year 5 of the COMPASS host study (2016-2017), four gender-stratified ordinal logistic regression models were used to examine how total STSB and four different types of STSBs (watching/streaming TV shows/movies, playing video games, Internet use, emailing/messaging/texting) are associated with frequency of cannabis use. Results: One-quarter of participants (24.9%) reported using cannabis in past 12 months; the largest proportion of this group (37.9%) reported rare/sporadic use. Overall, participants spent an average 7.45 ( ±5.26) hours/day on STSBs. Total STSB was positively associated with more frequent cannabis use, and when separated by type, internet use and messaging were significant. Playing video games and watching TV/movies were also significantly associated with more frequent cannabis use, but only for females. Conclusions: The associations between frequency of cannabis use and various measures of STSBs suggest that screen time may be a risk factor for cannabis use among youth. This association may be mediated by youths' mental wellbeing, given emerging evidence that STSB is a risk factor for poor mental health, and the tendency for individuals to use substances as a coping mechanism. Further, the ubiquity of pro-substance use content on the internet may also contribute to increased exposure to and normalization of cannabis, further promoting its use. Keywords: Youth health, Substance use, Risk behaviours, Cannabis, Screen time